High-Stability and Compact Interference Image Detection With Quasi-Real-Time Calibration Based on Phase Feedback Compensation - Meiling Guan; Yang Liu; Hongman Zhang; Xuefei Liu; Hemeng Xue; Yansheng Hao; Xiaowen Li; Zhengyu Ye; Ze Zhang (IEEE Photonics Journal, 2025)
We propose a high-stability compact interference image detection by an adjustable baseline with real-time calibration based on phase feedback compensation, which is formed by traditional lens pairing. A theoretical model of the interference detection system is established to analyze the effect of reconstruction. The jitter of interference signal caused by environmental disturbance is solved effectively by phase feedback compensation and the corresponding fluctuations is less than 1.06%. The interferometric detection system can switch between the detection mode and the calibration mode through the optical switch. Three targets are successfully reconstructed with different baseline interference data. The relative position error between the calculated coordinates and the measured coordinates of the point target is less than 4%. Such the high stability interference detection system has good prospect for fast aiming interconnection of optical communication and electro-optical reconnaissance.